(untitled) (Bangladesh Veterinarian, 2017)
Different concentrations of dimethyl sulfoxide (DMSO) and glycerol were used for cryopreservation of Vero cells. After total cell count Vero cells were preserved in liquid nitrogen. Two frozen stocks were made simultaneously from the cell suspensions of same concentrations using DMSO or glycerol at concentrations of 2.5%, 5%, 10% and 15%. After six months of cryopreservation both frozen stocks were used providing same nutrients and environment for the viability of the Vero cells. The cell viability analysis was performed immediately after thawing by Trypan Blue Exclusion Test. Both cryoprotectants showed a protective effect on Vero cells. When Glycerol was used, a maximum cell viability rate of 89.4% and a lowest cell viability rate of 63% were achieved at concentrations of 10% and 2.5%, respectively. On the other hand, DMSO at a concentration of 10% had the highest effect on cryoprotectivity and showed highest cell viability (75%), while at 15% concentration it showed the lowest cell viability (53%). It is suggested that DMSO and glycerol are appropriate protective materials for the cryopreservation of Vero cells. The solutions at concentration of 10% of DMSO and glycerol could be the best choice of cryoprotectant for long-term (6 months) preservation of Vero cells. Bangl. vet. 2016. Vol. 33, No. 1, 1-7